Principal's Leadership Strategy in Improving the Quality of Education - Asirah, Wardatul; Alauddin, Alauddin; Asafari, Amir Fqihuddin; Annisa, Annisa (Educational Journal of Learning Technology, 2024)
This study explores the leadership strategy of school principals in improving the quality of education at State Junior High School 1 Bua Ponrang. The research method used was in-depth interviews with the principal, vice principal for curriculum, and teachers at the school, as well as documentary studies to gain a thorough understanding of the implementation of the leadership strategy. The study results show that school principals implement democratic Leadership by holding various trainings and workshops to improve the professionalism of teachers. In addition, he is also active in managing the school curriculum to suit the needs and latest developments. The interpretation of the results shows that this approach has created a conducive learning environment, improved teacher performance, and improved the overall quality of education at State Junior High School 1 Bua Ponrang. The conclusion of this study is the need for continuity in developing educational human resources, strengthening responsive curriculum management, and the importance of participatory Leadership to achieve better educational goals.